ANALISIS DESKRIPSI FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN WISATAWAN PADA OBJEK WISATA TETETANA TOMOHON - Deisy Andih; Radjab Djamali; Fonny Sangari; Margaretha Warokka (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
Tetetana tourist attraction is one of the destinations for tourists who want to enjoy the natural scenery with a cool and comfortable climate. This object is located in Tomohon city, precisely in the vilĺage of Suluan. Although there are many tourist attractions that offer natural views and coolness in Tomohon City, the Tetetana tourist attraction remains a favourite destination for tourists. It is proven that there are so many tourist visits to this place, especially during holidays. This research was carried out using a quantirative descriptive method. Tourists' perception of this attraction was based on attractions consisting of the beauty of the Tetetana tourist attraction ,followed by friendliness. Tourists'perception of the Tetetana Tomohon tourist attraction based on accessibility( transportation) to the site shows that transportation to the location is very easily dominated. Tourists' perception based on amenities( facilities) are in the first place toilets, followed by gazebos and then parking lots. Meanwhile, the factors that encourage the tourists to visit the Tetetana Tomohon tourist attraction are the natural beauty, accompanying family and friends , followed by relaxation and rest and finally, see something different